2017
DOI: 10.3892/mmr.2017.8175
|View full text |Cite
|
Sign up to set email alerts
|

Prazosin protects myocardial cells against anoxia-reoxygenation injury via the extracellular signal‑regulated kinase signaling pathway

Abstract: Ischemic heart disease (including coronary arterial atherosclerosis, or vascular cavity stenosis or occlusion) remains the leading cause of disease-associated mortality worldwide. Prazosin, a receptor blocker of postsynaptic adrenaline, is essential in expanding peripheral arteries, which decreases peripheral vascular resistance, and regulates anti-hypertensive action. However, the mechanisms underlying the effects of prazosin have not been fully elucidated. The aim of the present study was to investigate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 42 publications
0
8
1
Order By: Relevance
“…Mammalian STE20-like kinase 1 (Mst1) regulates expression of FUNDC1 through the MAPK/ERK 1/2 -CREB pathway, which reduces mitochondrial apoptosis of cardiomyocytes and improves MIRI (Yu et al, 2019). Prazosin protects cardiomyocytes against inflammation, oxidative stress, and apoptosis by increasing expression and activity of ERK 1/2 (Wang et al, 2017a). Preconditioning with remifentanil reduces cell injury and death, and protects against H/R injury in adult rat cardiomyocytes.…”
Section: The Extracellular Signal-regulated Kinase 1/2 Signaling Pathmentioning
confidence: 99%
“…Mammalian STE20-like kinase 1 (Mst1) regulates expression of FUNDC1 through the MAPK/ERK 1/2 -CREB pathway, which reduces mitochondrial apoptosis of cardiomyocytes and improves MIRI (Yu et al, 2019). Prazosin protects cardiomyocytes against inflammation, oxidative stress, and apoptosis by increasing expression and activity of ERK 1/2 (Wang et al, 2017a). Preconditioning with remifentanil reduces cell injury and death, and protects against H/R injury in adult rat cardiomyocytes.…”
Section: The Extracellular Signal-regulated Kinase 1/2 Signaling Pathmentioning
confidence: 99%
“…TGF-β1 activates TGF-βR Ⅰ and then directly phosphorylates ShcA to induce the recruitments of Grb2 and Sos complex and finally induces the ERK1/2 activation ( Lee et al, 2007 ). Importantly, various drugs protect the heart against pathological remodeling by regulating the ERK1/2 signaling pathway ( Zhang et al, 2016 ; Tang et al, 2018 ; Wang et al, 2018 ). Our data showed that KLX was able to inhibit the upregulation of phosphorylated ERK1/2 expression significantly in mouse hearts after TAC operation, which indicated that TGF-β1/ERK1/2 noncanonical but not TGF-β1/Smads canonical pathway was involved in the antifibrosis effect of KLX on hearts of pressure overload mice ( Figure 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…The non-selective α 1 -AR antagonist prazosin has been shown to ameliorate experimental autoimmune encephalomyelitis (23). In a preclinical model of ischemia-reperfusion injury, prazosin administration resulted in decreased expression of IL-6, TNF-α, IL-10, and IL-1, and prevented mortality (24). Finally, α 1 -AR antagonism has been shown to block cytokine production in human peripheral blood mononuclear cells from patients with juvenile polyarticular arthritis, and treatment with doxazosin abrogated catecholamine-augmented secretion of IL-6 (25).…”
Section: Discussionmentioning
confidence: 99%